Truncation of the scattering phase matrix for vector radiative transfer simulation. (November 2016) - Hioki, Souichiro; Yang, Ping; Kattawar, George W.; Hu, Yongxiang
Abstract: This short communication interprets the delta-fit technique in a context of similarity transformation and the correction to the source function, and derives the analogous form of the method to be applied for the scattering phase matrix. To adapt the delta-fit method to vector radiative transfer, the mathematically exact form of the similarity principle is used in the theoretical development. Some examples of relevant radiative transfer simulations are also presented for atmospheric ice particles. The performance of the adopted delta-fit method is comparable to the delta-M method with single scattering correction except for worse delta-fit performance for polarized radiance calculations in forward directions. Highlights: The delta-fit method is extended to the vector radiative transfer simulation. The theoretical background of the traditional delta-fit method is recapitulated in the context of similarity transformation. Radiative transfer simulations of an ice cloud layer are performed to evaluate the accuracy of the vectorized delta-fit method.